Some geometric properties of a new difference sequence space involving lacunary sequences - Karakaş, Murat; Et, Mikail; Karakaya, Vatan (My University, 2013)
In this paper, we define a new generalized difference sequence space involving lacunary sequence. Then, we examine k-NUC property and property (?) for this space and also show that it is not rotund where p = (pr) is a bounded sequence of positive real numbers with pr ? 1 for all r ? ?. © 2013 Wuhan Institute of Physics and Mathematics.
Keywords: Difference sequence space; K-NUC property; Lacunary sequence; Luxemburg norm; Rotundity